2013
DOI: 10.1103/physrevb.87.205416
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin relaxation in bilayer graphene

Abstract: Electron spin relaxation due to the D'yakonov-Perel' mechanism is investigated in bilayer graphene with only the lowest conduction band being relevant. The spin-orbit coupling is constructed from the symmetry group analysis with the parameters obtained by fitting to the numerical calculation according to the latest report by Konschuh et al. [Phys. Rev. B 85, 115423 (2012)] from first principles. In contrast to single-layer graphene, the leading term of the out-of-plane component of the spin-orbit coupling in b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
74
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 112 publications
(295 reference statements)
0
74
2
Order By: Relevance
“…Actually it was reported that band structure of silicene deposited on Ag(111) drastically modified by the hybridization between the silicon and silver atoms, and the silicene loses its Dirac fermion characteristics due to substrate-induced symmetry breaking [37]. The effect of the hybridization between silicene and metals was supported by the theoretical calculations [38,39].…”
Section: Introductionmentioning
confidence: 92%
“…Actually it was reported that band structure of silicene deposited on Ag(111) drastically modified by the hybridization between the silicon and silver atoms, and the silicene loses its Dirac fermion characteristics due to substrate-induced symmetry breaking [37]. The effect of the hybridization between silicene and metals was supported by the theoretical calculations [38,39].…”
Section: Introductionmentioning
confidence: 92%
“…Unfortunately, spin relaxation in graphene structures has been a baffling problem [3]. While experiments in both single layer graphene (SLG) [4][5][6][7][8][9][10][11] and bilayer graphene (BLG) [7,8] yield spin lifetimes on the 100-1000 ps time scale (the highest values achieved in graphene/h-BN structures [12,13]), theories based on realistic spin-orbit coupling and transport parameters predict lifetimes on the order of microseconds [14][15][16][17][18][19][20][21][22][23][24].While the magnitudes of the spin-relaxation rates of SLG and BLG are similar, the dependence of the rates on the electron density is opposite in the two systems. In SLG the spin-relaxation rate decreases with increasing the carrier density [5][6][7][8], in BLG the spin-relaxation rate increases [7,8].…”
mentioning
confidence: 99%
“…Contribution from spins inside diamond have been studied intensely and understood clearly. 21,33 In the following, we simply assumed that the contribution from spins inside is the same as that in bulk diamond with the same density of N as in the NDs used in this work and designated the corresponding transverse relaxation time of the NV center in bulk diamonds as T 2, bulk , According to the Redfield theory, 28,29 and taking into account of the influence of all the surface spins, in the limit of very short correlation time τ c T 2 , the transverse spin relaxation time T 2 of the NV center in NDs can be expressed as…”
mentioning
confidence: 99%
“…As reported previously, the transverse relaxation time is sensitive to the distribution or configuration of the P1 centers and 13 C nuclear spins. 33,34 To reach a more precise simulation results, the third term in Eq. (4) need be modified.…”
mentioning
confidence: 99%
See 1 more Smart Citation